Assessment of Skin Carotenoids among School Children - Thapa, Raba; Ruit, Sanduk; Bernstein, Paul S (Journal of Nepal Health Research Council, 2025)
Background: This study aimed to assess skin carotenoid measurement among children in the Hill region of Nepal. Methods: School children between 3 to 7 years old from six schools were enrolled in the study. Skin carotenoid levels were assessed using the Veggie Meter® (Longevity Link Corporation, Salt Lake City, Utah, USA). Detailed eye evaluations were conducted in subjects with low skin carotenoid scores (<150 Reflectance Units(RU)) and/or those with a history of night blindness. Results: A total of 324 school children were enrolled in the study with mean age of 5.12±1.33 years. The mean skin carotenoid score was 163±71 RU, ranging from 1 to 363 RU. The skin carotenoid level was <150 RU in 46.9% of children and between 150 and 200 RU in 23.5% of children. Low skin carotenoid scores (<150 RU) were found in 17% of 3 year olds, 28.3% each of 4 and 5 year olds, 20.4% of 6 year olds, and 11.2% of 7 year olds. In multivariate analysis, age was significantly associated with low skin carotenoid scores (p=0.003; OR; 2.02; 95% CI: 1.28- 3.19). Odds of having <150 RU was 2.02 times more among the children up to five years old as compared to those over five years of age. Conclusions: Nearly half of the school children had low skin carotenoid scores. Skin carotenoid score was significantly lower among the lower age group. These findings emphasize the need to enhance awareness to consume plenty of green leafy vegetables and fruits in the diet. Keywords: Children; Nepal; skin carotenoid; veggie meter; vitamin A.